Feminisme Islam dalam Perspektif Raden Ajeng Kartini - Isnawati, Reni; Isnaini, Elsa (Universitas Islam Negeri Raden Intan Lampung, 2022)
Abstract;Feminism is often seen as a women's injustice movement in an effort to seek justice for women. The status of men and women is the same, but often the status of men is higher than that of women. Islamic feminism emerged because society was unfair in treating women. One of those who fought for feminism in Indonesia was R.A Kartini (1879 – 1904) who was one of the proud national figures of the Jepara people. Her thoughts and hard work for the advancement of women made her recognized as a hero of women's emancipation. Kartini's struggle for feminism gave results that women can feel today, namely being able to pursue education on a par with men in terms of obtaining education. Because of its connection to the rise of feminism in Indonesia, the author is interested in discussing Islamic feminism from the perspective of Raden Ajeng Kartini. This research uses the library research method by using R.A Kartini's work as a primary source. The results of the writing show that in his thoughts regarding education for women it does not conflict with Islamic values. In fact, in a hadith, the Prophet Muhammad said,